William Holmes Walker papers - Walker, William Holmes, 1820-1908.
Memoir, diary, notebook, and scrapbook reflecting the history of the Mormon Church and Walker's life as an early Mormon convert and patriarch of the Mormon Church. In his memoir, Walker describes his years in Joseph Smith's household in the Mormon settlement of Nauvoo, Ill.; Walker's journey to South Africa and his missionary service there; the Mormon emigration from Nauvoo, Ill., to Salt Lake City, Utah following Smith's death in 1844; Walker's service in the U.S. Army Mormon Battalion in Iowa, Kansas, New Mexico, and Colorado; pioneer life, agriculture, and sawmills in Salt Lake City; evasion of federal authorities prosecuting Mormon polygamists during the 1880s; and Walker's life as a business and property owner and head of families in Utah and Idaho. In his diary, Walker documents his three years as a missionary in South Africa. The notebook, containing correspondence, copies of orders, and lists of officers, concerns the military preparedness of Salt Lake City and possible arrival of the U.S. military in 1857. Walker's son-in-law, Lewis E. Lauritzen, compiled the Walker family scrapbook.
Mormon convert and missionary.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Smith, Joseph, -- Jr., -- 1805-1844.; Lauritzen, Lewis E., -- 1878-1975.; Walker family; United States. -- Army. -- Mormon Battalion; Agriculture -- Utah -- Salt Lake City; Business enterprises -- Idaho; Business enterprises -- Utah; Frontier and pioneer life -- Utah -- Salt Lake City; Frontier and pioneer life -- Illinois -- Nauvoo; Missionaries -- South Africa; Mormon Church; Mormons -- Idaho; Mormons -- Illinois -- Nauvoo; Mormons -- South Africa; Mormons -- Utah -- Salt Lake City; Overland journeys to the Pacific; Polygamy -- United States; Real property -- Idaho; Real property -- Utah; Sawmills -- Utah -- Salt Lake City; Colorado -- Description and travel; Illinois -- History -- 1778-1865.; Idaho -- Description and travel; Idaho -- Social life and customs; Iowa -- Description and travel; Kansas -- Description and travel; Nauvoo (Ill.) -- Expulsion of the Mormons; Nauvoo (Ill.) -- History; New Mexico -- Description and travel; South Africa -- Description and travel; Utah -- Description and travel; Utah -- History; Utah -- Social life and customs; Missionaries